Kozmopolitski skladatelj nemirna duha - Martinčević, Jagoda (Array, 2008)
Milko Kelemen was born March 30th, 1924, in Podravska Slatina. He went to school in his native town and in Virovitica, and completed his studies of composing at the Music Academy in Zagreb in the class of Professor Stjepan Šulek and piano with Professor Melita Lorković. In 1961 he founds the Zagreb Music Biennale, a festival of contemporary music that saw massive success and is still active. Kelemen was its first president and is now its honorary president. Founder of the Music Biennale, teacher, researcher of electro-acoustics, writer, adventurer and passionate seeker for the unfathomable – composer Milko Kelemen taught composition abroad at the Robert Schumann Institute in Duesseldorf, and subsequently at the College of Music in Stuttgart. This musical artist is also active as a visiting lecturer at universities in Montreal, Buenos Aires and Rio de Janeiro. He is the recipient of numerous eminent awards and commendations, among others the Vladimir Nazor Award for Lifetime Achievement, the Beethoven Award in Bonn, the French decoration Chevalier des arts et des lettres. At this year's Zagreb Music Biennale, held April 26th, Dieter Topp, the president of the European Culture Forum, conferred upon Milko Kelemen the 2007 Europe Culture Award. Kelemen's first international breakthrough with the composition Concert Improvisations, performed by the celebrated Zagreb Soloists under Antinio Janigro, will certainly be remembered in music history. In just a few years the Zagreb Soloists performed Kelemen's composition several hundred times around the world. The composition has been performed over 600 times since then. The work of Milko Kelemen includes compositions of all kinds, from chamber music, solo pieces and symphonies to operas. It is in music that his personality as an author comes perhaps most to the fore, melding the composer, writer and philosopher, contemplating and commenting the world and phenomenon that surround him.